Unlearning Human Rights and False Grand Dichotomies? - Hamzić, Vanja (2011)
This paper offers a brief genealogical analysis of sexual and gender diversity in Indonesia. It traces various streams of regulation, including those reliant on liberal legalistic discourse of human rights. It is argued that this discourse remains inapt to account for numerous local identitary frictions, transitions and re-appropriations owed, inter alia, to distinct non-sexual and non-gender communitarian dynamics. Instead, it continues to usher in an alien dichotomy of personhood, whose referential, idealised ‘self’ and juxtaposed ‘other’ are both violently simplified and tainted with heightened ideological overtones.